Answer:
![y=-1](https://tex.z-dn.net/?f=y%3D-1)
Step-by-step explanation:
We have been given an equation
. We are asked to complete the given table using our given equation.
We can see that our given table has two columns namely x and y.
To find the value of y for given values of x, we need to substitute the given x value in our equation.
Substituting
in our equation we will get,
![y=-2*0+1](https://tex.z-dn.net/?f=y%3D-2%2A0%2B1)
![y=0+1](https://tex.z-dn.net/?f=y%3D0%2B1)
![y=1](https://tex.z-dn.net/?f=y%3D1)
Therefore, the value of y for first row is 1 and ordered pair will be (0,1).
Substituting
in our equation we will get,
![y=-2*-3+1](https://tex.z-dn.net/?f=y%3D-2%2A-3%2B1)
![y=6+1](https://tex.z-dn.net/?f=y%3D6%2B1)
![y=7](https://tex.z-dn.net/?f=y%3D7)
Therefore, the value of y for 2nd row is 7 and ordered pair will be (-3,7).
Substituting
in our equation we will get,
![y=-2*1+1](https://tex.z-dn.net/?f=y%3D-2%2A1%2B1)
![y=-2+1](https://tex.z-dn.net/?f=y%3D-2%2B1)
![y=-1](https://tex.z-dn.net/?f=y%3D-1)
Therefore, the value of y for 3rd row is
and ordered pair will be (1,-1).